(untitled) (Boletín Epidemiológico Semanal, 2024)
Introduction: Rabies is a highly lethal zoonosis caused by various types of Lyssavirus, and transmitted to humans mainly by dogs. Spain has been free of terrestrial rabies on the peninsula and islands since 1978, but sporadic cases in animals are reported in Ceuta and Melilla, and some imported human cases. The objective was to describe the cases of this disease in humans and terrestrial animals in Spain in the 21st century. Method: A descriptive analysis of rabies cases in Spain from 2000 to 2023 was performed, based on notification to the Spanish National Epidemiology Network (RENAVE). For humans, the variables analyzed were sex, age, place of residency, type of virus, transmitting animal, vaccination, and mortality; for terrestrial animals, only the species were described. Results: During the study period, 2 human cases of rabies were reported, one in 2014 and other in 2019, both imported from Morocco. In terrestrial animals, 80 cases were declared, most in dogs, all of them in Ceuta and Melilla except for one case imported into the peninsula. Conclusions: Rabies is a controlled disease in Spain. It is important to maintain adequate prevention, surveillance and control to avoid re-emergence into our country.